A labour of Sisyphus? Public policy and health inequalities research from the Black and Acheson Reports to the Marmot Review. Issue 5 (4th November 2010) - Bambra, C; Smith, K E; Garthwaite, K; Joyce, K E; Hunter, D J
Abstract : Objectives: To explore similarities and differences in policy content and the political context of the three main English government reports on health inequalities: the Black Report (1980), the Acheson Enquiry (1998), and the Marmot Review (2010). Methods: Thematic policy and context analysis of the Black Report (1980), the Acheson Enquiry (1998), and the Marmot Review (2010) in terms of: (i) underpinning theoretical principles; (ii) policy recommendations; (iii) the political contexts in which each was released; and (iv) their actual or potential influence on research and policy. Results: There were great similarities and very few differences in terms of both the theoretical principles guiding the recommendations of these reports and the focus of the recommendations themselves. However, there were clear differences in terms of the political contexts of each report, as well as their subsequent impacts on research and policy. Conclusion: The paper calls into question the progress of health inequalities research, the use of evidence and of the links between research, politics and policy.